A NOVEL RESOURCE CONSTRAINT SECURE(RCS) ROUTING PROTOCOL FOR WIRELESS SENSOR NETWORK - R. GEETHA (Journal of Engineering Science and Technology, 2017)
Geographic routing protocols are the most preferred routing protocols for Wireless Sensor Networks (WSN) since they rely on geographic position information. Hence we propose geography based Resource Constraint Secure routing (RCS) protocol. The existing routing protocol named Cost Aware SEcure Routing (CASER) allows messages to be transmitted using random walking routing strategy. In the Random walking method, there is a chance of choosing low energy node as a relay node. RCS protocol overcomes this by transmitting the data via energy aware route only and it provides authentication by using Modified ElGammal Signature (MES) scheme on Elliptic curve algorithm. For security purposes, the content of each message can also be encrypted by using a symmetric key encryption technique and decoded at the sink node by knowing the same secret key used by the source. So, unauthenticated person cannot access the original data. Therefore the protocol ensures a secure message delivery option to maximize the message delivery ratio under adversarial attacks. The performance evaluation results show that RCS performs better than CASER with respect to Packet Delivery Ratio, Energy Balance Factor and End-to-End Delay, Throughput and Routing overhead.